Zum Gedenken an Peter Borowsky - Hering, Rainer; Nicolaysen, Rainer (Hamburger Universitätsreden Neue Folge, 2003)
On October 13, 2000 the historian Peter Borowsky, a "pupil" of Fritz Fischer, died at the age of 62. He has worked at the University of Hamburg for almost four decades: as a student, research assistant, senior scientific officer and private lecturer for modern and contemporary history. In 1996, he was awarded the title of "Professor"; however, he was denied a professorship. As an author of high-circulation historical works, Peter Borowsky reached a large audience. Written jointly with Barbara Vogel and Heide Wunder, the introduction to history first published in 1975 is still a scientific "best-seller"to this day; Borowsky's Hitler biography for young people and his overview of German history after 1945 also experienced numerous editions. However, the focus of his work was on academic teaching, in which he achieved outstanding results. Generations of history students were taught, supervised and shaped by him - at the University of Hamburg as well as at Smith College, Northampton/Massachusetts, where the scholar has regularly held a visiting professorship since 1974. The partnership between these two universities was embodied by Peter Borowsky. The academic commemoration ceremonies in his honour - in February 2001 at the University of Hamburg and the following month at Smith College - conveyed a moving impression. A selection of the speeches given there and previously at the funeral service at the Nienstedten cemetery is summarized in this booklet. At the same time, an extensive commemorative volume was published on June 3, 2003, the 65th anniversary of Peter Borowsky's birth, the title "Lebendige Sozialgeschichte. Borowskys Forschungsfelder" (Living Social History. Borowskys Research Fields) is intended to emphasize the content and methodology of Borowsky's work and at the same time to accentuate his special way of conveying history.